The Dancers’ Visuospatial Body Map Explains Their Enhanced Divergence in the Production of Motor Forms: Evidence in the Early Development - Palmiero, Massimiliano; Giulianella, Luna; Guariglia, Paola; Boccia, Maddalena; D’Amico, Simonetta; Piccardi, Laura (Frontiers in Psychology, 2019)
Dance represents an opportunity to promote not only motor skills but also other cognitive functions and general well-being. In this study 58 children aged 6-10 years were enrolled in order to test the issue if dance improves divergent thinking in motor and visual domains (domain-general and specificity hypotheses), and whether the topological map of the body mediates the performance at the motor task (mediation hypothesis). At the aim, 33 children practicing dance were compared with a control group (25 children). Children were administered the visual divergent thinking task of the Torrance Test of Creative Thinking, consisting in making drawings starting from given shapes, and the motor-form divergent thinking task, opportunely developed consisting in producing acted motor forms in the extrapersonal space. Both tasks were presented for 10 minutes and were scored in terms of fluency, flexibility and originality. The ability to form the topological map of the body was measured by the frontal body-evocation test. Results revealed that children practicing dance outperformed the control group only in terms of the ability to perform motor forms. In addition, dancers showed a better topological map of the body, and, most importantly, besides the direct effect of group on the ability to produce acted motor forms, a significant indirect effect of the group, mediated by performances on frontal body-evocation task, was found. These results have important implications for cognition, showing that dance can improve the topological map of the body that in turn enhances creativity in motor domain since the early developmental age.